PENGARUH RETURN ON ASSET (ROA), LOAN TO DEPOSIT RATIO (LDR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK PERIODE 2013-2022 - Aulia, Shifa; Sanjaya, Rudi (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Return on Assets (ROA), Loan to Deposits Ratio (LDR) and Debt to Equity Ratio (DER) on Stock Prices at PT Bank Rakyat Indonesia (PERSERO) Tbk 2013-2022 Period partially or simultaneously. The research method and type of data used are quantitative methods and secondary data, while the sample in this study is the financial statements in the form of balance sheets, profit and loss and Stock Price of PT Bank Rakyat Indonesia (PERSERO). The data analysis method used is financial ratio analysis and quantitative analysis. Furthermore, hypothesis testing uses the t test and f test. The results of this study indicate that Return on Assets (ROA) partially has no effect on the share price of PT Bank Rakyat Indonesia (PERSERO) Tbk 2013-2022, the Loan to Deposits Ratio (LDR) variable partially has no effect on the share price of PT Bank Rakyat Indonesia (PERSERO) Tbk 2013-2022, Debt to Equity Ratio (DER) partially affects the share price of PT Bank Rakyat Indonesia (PERSERO) Tbk 2013-2022. Return on Assets (ROA), Loan to Deposits Ratio (LDR) and Debt to Equity Ratio (DER) simultaneously affect the stock price of PT Bank Rakyat Indonesia (PERSERO) Tbk 2013-2022.